Longevity of erythrocytes in anemia of Carrion's disease - Reynafajd, César (1959)
Anemia of Carrion's disease is due to increased destruction of red blood cells, as has been noted in previous studies (1,2,3,4,5,6). In all ellasm however, have been used to demonstrate the study of the decomposition products of hemoglobin, or eritrofagocilosis histological observation. But it has not made ​​a direct study of the red blood cell, as regards their stay in the bloodstream; nor has a quantitative estimate of their removal by the organs of reticuloendtelial system.